Walt disney classics the tigger movie (Grolier Books Danbury, Connecticut, 2000)
Tigger, the energetic and bouncy tiger from the Hundred Acre Wood, feels lonely and sets out to find other Tiggers like himself. Along the way, his friends$1 (BWinnie the Pooh, Piglet, and others$1 (Bshow him how much they care. The movie celebrates friendship, belonging, and the importance of being yourself.s